A novel low-frequency wave-absorbing material and a preparation method thereof

CN122978780APending Publication Date: 2026-10-27ANHUI MINGXUN NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411428518.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

由于金属粉末添加比例的限制,使复合材料的磁导率偏低(在1GHz 时小于5)

Benefits of technology

[0023]有益效果:本发明开发出一种低频吸波材料,通过对铁锌合金粉表面进行包覆处理,获得自组装氨基硅烷薄膜,一方面改善了微波吸收剂与树脂间得界面特性,制得兼具高韧性的低频吸波软磁层;另一方面,有效改善了所述吸波材料在应用时的电磁波阻抗匹配性能,使得低频吸波性能更稳定、更突出。将所得含有微波吸收剂的涂料喷涂到PET双面胶上,提高了吸波材料的加工性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a novel low-frequency wave-absorbing material and a preparation method thereof, and the novel low-frequency wave-absorbing material is composed of a PET double-sided adhesive as a base layer and a coating layer containing microwave absorber fillers. The microwave absorber fillers are prepared by surface coating treatment of a flaky composite ferromagnetic material containing iron and aluminum with amino silane, and the microwave absorber fillers account for 45-70% of the mass of the coating layer. The obtained material has high magnetic permeability and low low-frequency loss at 1-4 GHz, and good flexibility and processability, so that the material can be widely applied to electromagnetic radiation response of various electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite materials, and more specifically, to a novel low-frequency absorbing material and its preparation method. Background Technology

[0002] Absorbing electromagnetic shielding materials have unique applications in the electromagnetic compatibility of electronic devices. They can not only prevent the leakage of electromagnetic waves, but also do not reflect electromagnetic waves, thus avoiding interference with the components of the device itself.

[0003] Currently, there are many types of materials that can be used as microwave absorbers, such as various ferrite powders, carbonyl iron powder (CIP), FeCo alloy powder, polycrystalline iron fibers, and ultrafine metal powders. Fe group metals and alloy powders are currently the most widely researched and applied microwave absorbers both domestically and internationally. They possess high magnetic permeability and certain dielectric properties, showing promising prospects for expanding the effective absorption bandwidth. For example, absorbing materials prepared from resin / magnetic powders, with a thickness of 1 mm, can achieve absorption effects of over -20 dB in the 8-18 GHz frequency band, and have been applied in radar stealth and electromagnetic compatibility of electronic equipment. However, for the low-frequency band (1-4 GHz), due to the low magnetic permeability of the material, the absorption performance is poor when the thickness is thin.

[0004] High-performance microwave absorbing materials require high permeability and magnetic loss. Ferrite materials, limited by Snoke's law, have relatively low permeability (less than 2) in the 1-4 GHz range. Ferromagnetic metal absorbers (including iron powder, iron-cobalt alloy powder, iron nitrides, etc.) have high saturation magnetization and high intrinsic permeability in the microwave band (theoretically around 20 in the 1-4 GHz range). However, as good conductors, they must be dispersed within an insulating medium to exhibit overall insulating properties in order to achieve microwave absorption. The addition of the dielectric phase significantly reduces the permeability of the composite material. Theoretically, the more magnetic metal phase added, the better for increasing permeability. However, when the amount of metal phase added exceeds a certain value (percolation threshold), the prepared metal-dielectric composite material becomes a conductor, similar to the reflective phase of a bulk metal sample, strongly reflecting microwave radiation and thus unsuitable for use as a microwave absorbing material. The percolation threshold of composite materials is closely related to the raw materials and preparation process. The volume fraction, morphology and distribution of metal powder have a great influence on magnetic permeability and dielectric constant. The more uniform the distribution of the metal phase and the dielectric phase, the higher the percolation threshold of the metal-dielectric composite material.

[0005] For epoxy resin / magnetic metal powder systems, using conventional mixing methods, the percolation threshold of the composite material is difficult to exceed 45%. When the proportion of metal powder added is greater than this, the metal powder particles tend to aggregate to form a conductive network, making the composite material as a whole conductive. Due to the limitation of the proportion of metal powder added, the magnetic permeability of the composite material is relatively low (less than 5 at 1 GHz).

[0006] The microwave absorbing materials described above belong to the category of load-bearing absorbing materials. They possess excellent microwave absorption performance along with good mechanical properties. The absorbing agent in load-bearing absorbing materials can be added to the matrix as a reinforcing phase. Coating-type absorbing materials also exist, which use a phase with excellent microwave absorption performance as the absorbing agent and a binder as the matrix, and are coated onto the surface of the target object. However, load-bearing absorbing materials have higher requirements for molding processes and higher production costs, while coating-type absorbing materials have advantages such as simpler production processes and greater adjustability. In lower-temperature applications, they have greater practical application value than load-bearing absorbing materials.

[0007] However, regardless of the structure of the microwave absorbing composite material, improving the intrinsic permeability of the magnetic metal powder is the key to improving the permeability of the composite material, thereby achieving a high microwave absorption rate even with a thinner thickness. Summary of the Invention

[0008] The purpose of this invention is to provide a novel low-frequency absorbing material. This material has high permeability in the 1-4GHz range, low loss, good flexibility and processability, and can be used to cope with electromagnetic radiation in various electronic devices.

[0009] A novel low-frequency microwave absorbing material comprises a PET double-sided adhesive substrate and a coating containing a sheet-like microwave absorber. The coating containing the microwave absorber uses acrylic resin, amino resin, and cellulose resin as the matrix and sheet-like iron-aluminum alloy modified by an aminosilane surface coating process as the sheet-like microwave absorber filler.

[0010] In some embodiments of the present invention, the method for preparing the microwave absorber includes the following steps: S1: Mix zinc sulfate and ferrous sulfate according to Zn 2+ Fe 2+ The ferric zinc alloy powder is prepared by dissolving a metal ion in deionized water at a molar ratio of 0.25-0.30:0.7-0.75 to form a salt solution with a metal ion concentration of 1 mol / L. NaOH is added to the hydrazine hydrate solution to adjust the pH of the mixed solution to 8-12. The solution is then heated to 80-100℃, and the salt solution is added dropwise. The mixture is kept at this temperature for 0.5-1.5 hours. After the solution has completely changed color, the precipitate is filtered, washed until neutral, and the resulting powder is dried to obtain iron-zinc alloy powder. S2: Using methanol as a solvent, prepare an aminosilane solution with a volume fraction of 2-5%. Then, add the iron-zinc alloy powder obtained in S1 to the aminosilane solution at a mass ratio of 1:2.5-4. Stir and react for 24 hours to obtain a mixed slurry. S3: After filtering, washing, and drying the mixed slurry obtained in S2 with high-concentration nitrogen, the resulting paste is dried, crushed, and sieved in a constant temperature and atmospheric pressure environment to obtain the microwave absorber.

[0011] Further, the aminosilane mentioned in S2 is at least one of 3-aminopropyltrimethoxysilane, N-methyl-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, di(3-trimethoxysilylpropyl)amine, N,N-diethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropyltriethoxysilane, and N-methyl-3-aminopropyltriethoxysilane.

[0012] Furthermore, the drying temperature described in S3 is 80-100℃, and the drying time is 6-8h.

[0013] In some embodiments of the present invention, the method for preparing the coating containing the microwave absorber includes the following steps: SS1: Add the organic solvent into the reactor and stir until homogeneous. Then add the cellulose resin and stir for 1-2 hours until completely dissolved. Then add the acrylic resin and amino resin in sequence and stir for 1-3 hours until fully mixed. SS2: Add the microwave absorber to the resin system obtained in SS1 and stir until it is evenly dispersed; SS3: Add the functional additive to the reaction vessel and stir evenly to obtain the coating containing the microwave absorber.

[0014] Furthermore, the organic solvent mentioned in SS1 is at least one of acetone, isopropanol, n-butanol, propylene glycol methyl ether, ethyl acetate, and n-butyl acetate, and is used in a mass percentage of 8-25% of the coating containing the microwave absorber.

[0015] Further, the acrylic resin in SS1 has an acid value of 7-9 mgKOH / g and is used at a mass percentage of 10-15% of the coating containing the microwave absorber; the cellulose resin is obtained by mixing cellulose acetate butyrate and cellulose acetate propionate in a mass ratio of 0.5-1.7:1-5 and is used at a mass percentage of 1-5% of the coating containing the microwave absorber; the amino resin is urea-formaldehyde resin and is used at a mass percentage of 5.5-10% of the coating containing the microwave absorber.

[0016] Furthermore, the microwave absorber used in SS2 is 45-70% by mass of the coating containing the microwave absorber.

[0017] Furthermore, the functional additives described in SS3 include at least one of leveling agents, softening agents, and drying agents.

[0018] In this invention, microwave absorbers are mixed with coatings as fillers and creatively combined with PET double-sided adhesive to enable their simple use inside various precision electronic devices, thereby preventing internal electromagnetic interference. However, the interfacial properties between the microwave absorber and the resin affect the overall physicochemical properties of the microwave absorber, resulting in a decrease in the toughness and elasticity of the resulting coating. Furthermore, the anisotropic nature of sheet-like microwave absorbers makes them prone to irregular stacking, forming pores, which further degrades the overall toughness and elasticity of the coating. Therefore, this invention performs surface coating treatment on the prepared iron-zinc alloy powder to improve the interfacial continuity between the microwave absorber and the resin, and combines it with an organic polymer resin with good toughness and elasticity as a matrix to prepare a microwave-absorbing soft magnetic coating, effectively improving the overall toughness and elasticity of the microwave-absorbing coating.

[0019] In preparing the microwave absorber, a specially structured aminosilane is preferred. The aminosilane self-assembles on the surface of the iron-zinc alloy to form a thin film. This film has a high dielectric constant, which effectively improves electromagnetic wave impedance matching performance and further enhances low-frequency absorption performance, making the low-frequency absorption performance more stable and outstanding. The different mass ratios of aminosilane to iron-zinc alloy powder directly affect the low-frequency absorption effect of the resulting absorbing material. Within the mass ratio range provided above, absorbing materials with high permeability at 1-4 GHz can be obtained.

[0020] The preparation method of the novel low-frequency absorbing material described above includes the following steps: spraying a coating containing a microwave absorber onto the release film surface of PET double-sided adhesive, and curing it to obtain the novel low-frequency absorbing material.

[0021] In some embodiments of the present invention, the spraying method may be air spraying, airless spraying, classic spraying, high-pressure airless spraying, etc.

[0022] In some embodiments of the present invention, the curing method is to dry at 150-170°C for 15-40 seconds.

[0023] Beneficial Effects: This invention develops a low-frequency absorbing material. By coating the surface of iron-zinc alloy powder, a self-assembled aminosilane film is obtained. This improves the interfacial characteristics between the microwave absorber and the resin, resulting in a low-frequency absorbing soft magnetic layer with high toughness. Furthermore, it effectively improves the electromagnetic impedance matching performance of the absorbing material during application, making its low-frequency absorption performance more stable and outstanding. Spraying the obtained coating containing the microwave absorber onto PET double-sided adhesive improves the processability of the absorbing material. Detailed Implementation

[0024] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.

[0025] The preparation of the microwave absorber used in the embodiments is illustrated below: Microwave Absorber-1 S1: Mix zinc sulfate and ferrous sulfate according to Zn 2+ Fe 2+ The metal ions were dissolved in deionized water at a molar ratio of 0.25:0.7 to prepare a salt solution with a metal ion concentration of 1 mol / L. NaOH was added to a 3.5 wt% hydrazine hydrate solution to adjust the pH of the solution to 8. The solution was then heated to 80°C, and the salt solution was added dropwise. The solution was kept at this temperature for 1.5 h. After the solution color changed completely, the precipitate was filtered, washed until neutral, and the resulting powder was dried to obtain iron-zinc alloy powder. S2: Using methanol as a solvent, prepare 100 ml of a 20% (v / v) 3-aminopropyltrimethoxysilane solution (3-aminopropyltrimethoxysilane mass is 20.54 g). Then, add the iron-zinc alloy powder (m=8.22 g) obtained in S1 to the solution at a mass ratio of 1:2.5 with 3-aminopropyltrimethoxysilane. Stir and react for 24 h to obtain a mixed slurry. S3: The mixed slurry obtained in S2 is filtered, washed with methanol and deionized water, dried with high-concentration nitrogen, and then dried in a constant temperature environment of 80°C under normal pressure for 8 hours, crushed, and sieved to obtain the microwave absorber-1.

[0026] Microwave Absorber-2 S1: Mix zinc sulfate and ferrous sulfate according to Zn 2+ Fe 2+The metal ions were dissolved in deionized water at a molar ratio of 0.28:0.72 to prepare a salt solution with a metal ion concentration of 1 mol / L. NaOH was added to a 3.5 wt% hydrazine hydrate solution to adjust the pH of the solution to 10. The solution was then heated to 90°C, and the salt solution was added dropwise. The solution was kept at this temperature for 1 hour. After the solution color changed completely, the precipitate was filtered, washed until neutral, and the resulting powder was dried to obtain iron-zinc alloy powder. S2: Using methanol as a solvent, prepare 100 ml of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane solution with a volume fraction of 35% (the mass of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 35.98 g). Then, add the iron-zinc alloy powder (10.28 g) obtained in S1 to the solution at a mass ratio of 1:3.5 with 3-aminopropyltrimethoxysilane. Stir and react for 24 h to obtain a mixed slurry. S3: The mixed slurry obtained in S2 is filtered, washed with methanol and deionized water, dried with high-concentration nitrogen, and then dried in a constant temperature environment of 90°C under normal pressure for 7 hours, crushed, and sieved to obtain the microwave absorber-2.

[0027] Microwave Absorber-3 S1: Mix zinc sulfate and ferrous sulfate according to Zn 2+ Fe 2+ The metal ions were dissolved in deionized water at a molar ratio of 0.3:0.7 to prepare a salt solution with a metal ion concentration of 1 mol / L. NaOH was added to a 3.5 wt% hydrazine hydrate solution to adjust the pH of the solution to 12. The solution was then heated to 100°C, and the salt solution was added dropwise. The solution was kept at this temperature for 0.5 h. After the solution color changed completely, the precipitate was filtered, washed until neutral, and the resulting powder was dried to obtain iron-zinc alloy powder. S2: Using methanol as a solvent, prepare 100 ml of N-methyl-3-aminopropyltriethoxysilane solution with a volume fraction of 50% (the mass of N-methyl-3-aminopropyltriethoxysilane is 48.75 g). Then, add the iron-zinc alloy powder (12.19 g) obtained in S1 to the solution at a mass ratio of 1:4 with 3-aminopropyltrimethoxysilane. Stir and react for 24 h to obtain a mixed slurry. S3: The mixed slurry obtained in S2 is filtered, washed with methanol and deionized water, dried with high-concentration nitrogen, and then dried in a constant temperature environment of 100°C under normal pressure for 6 hours, crushed, and sieved to obtain the microwave absorber-3.

[0028] Microwave Absorber-4 The difference between this and microwave absorber-3 is that the aminosilane used is tert-butylpropylaminotrimethoxysilane.

[0029] Microwave Absorber-5 The difference is that the iron-zinc alloy powder and 3-aminopropyltrimethoxysilane have a mass ratio of 1:5.

[0030] Example 1 Paint preparation: SS1: Add 8% acetone to the reactor and stir until homogeneous. Then add 1% cellulose resin (cellulose acetate butyrate: cellulose acetate propionate = 0.5:1) and stir for 1 hour until completely dissolved. Then add 10% acrylic resin and 5.5% amino resin in sequence and stir for 1 hour until fully mixed. SS2: Add 70% of the microwave absorber-1 to the resin system obtained in SS1 and stir until evenly dispersed; SS3: Add 1.5% leveling agent polydimethylsiloxane, 2% softening agent (dibutyl phthalate: polyetheramine D2000 = 2:1) and 2% drying agent neodecanoic acid to the reaction vessel and stir evenly to obtain the coating containing microwave absorber.

[0031] Preparation of new low-frequency absorbing materials: The obtained coating is sprayed onto the release film of PET double-sided adhesive through air spraying, and then dried at 150°C for 15 seconds to obtain the novel low-frequency absorbing material.

[0032] Example 2 Paint preparation: SS1: Add 15% n-butanol to the reactor and stir until homogeneous. Then add 3% cellulose resin (cellulose acetate butyrate: cellulose acetate propionate = 1:3) and stir for 1.5 hours until completely dissolved. Then add 12% acrylic resin and 8% amino resin in sequence and stir for 2 hours until fully mixed. SS2: Add 60% of the microwave absorber-2 to the resin system obtained in SS1 and stir until evenly dispersed; SS3: Add 1% leveling agent polydimethylsiloxane, 0.5% softening agent (dibutyl phthalate: polyetheramine D2000 = 2:1) and 0.5% drying agent neodecanoic acid to the reaction vessel and stir evenly to obtain the coating containing microwave absorber.

[0033] Preparation of new low-frequency absorbing materials: The obtained coating is sprayed onto the release film of PET double-sided adhesive through air spraying, and dried at 160°C for 25 seconds to obtain the novel low-frequency absorbing material.

[0034] Example 3 Paint preparation: SS1: Add 21% propylene glycol ethyl ether to the reactor and stir until homogeneous. Then add 5% cellulose resin (cellulose acetate butyrate: cellulose acetate propionate = 1.7: 5) and stir for 2 hours until completely dissolved. Then add 15% acrylic resin and 10% amino resin in sequence and stir for 2 hours until fully mixed. SS2: Add 45% of the microwave absorber-3 to the resin system obtained in SS1 and stir until evenly dispersed; SS3: Add 1% leveling agent polydimethylsiloxane, 2.5% softening agent (dibutyl phthalate: polyetheramine D2000 = 2:1) and 0.5% drying agent neodecanoic acid to the reaction vessel and stir evenly to obtain the coating containing microwave absorber.

[0035] Preparation of new low-frequency absorbing materials: The obtained coating is sprayed onto the release film of PET double-sided adhesive through air spraying, and dried at 170°C for 40 seconds to obtain the novel low-frequency absorbing material.

[0036] Example 4 Same as Example 3, except that microwave absorber-3 is replaced with microwave absorber-4.

[0037] Example 5 Same as Example 3, except that microwave absorber-3 is replaced with microwave absorber-5.

[0038] Comparative Example 1 Same as Example 3, except that microwave absorber-3 is replaced with iron-zinc alloy powder that has not undergone surface coating treatment.

[0039] Comparative Example 2 Same as Example 3, except that microwave absorber-3 is not added.

[0040] Performance Testing: The low-frequency absorbing materials of each embodiment and comparative example were fabricated into rings with a thickness of 2 mm. The electromagnetic parameters (dielectric constant and permeability) were measured using an Agilent E5071C vector network analyzer. Then, the reflection loss was calculated and simulated. The test results are shown in Tables 1-1, 1-2, 1-3, 1-4, 1-5, 1-6, and 1-7.

[0041] The highest absorption at 2 mm, calculated based on the sample's electromagnetic parameters, occurred at 2.6 GHz, at -13 dB.

[0042]

[0043] The highest absorption at 2 mm, calculated based on the sample's electromagnetic parameters, occurred at 2.0 GHz, at -15 dB.

[0044]

[0045] The highest absorption at 2 mm, calculated based on the sample's electromagnetic parameters, occurred at 1.8 GHz, at -12 dB.

[0046]

[0047] The highest absorption at 2 mm, calculated based on the sample's electromagnetic parameters, occurred at 2.8 GHz, at -10 dB.

[0048]

[0049] The highest absorption at 2 mm, calculated based on the sample's electromagnetic parameters, occurred at 2.6 GHz, at -11 dB.

[0050]

[0051] The highest absorption at 2 mm, calculated based on the sample's electromagnetic parameters, occurred at 2.7 GHz, at -8 dB.

[0052]

[0053] The highest absorption at 2 mm, calculated based on the sample's electromagnetic parameters, occurred at 1.8 GHz, at -13 dB.

[0054] In the table, the real parts (μ′, ε′) of the electromagnetic parameters represent the ability to store electromagnetic wave energy, while the imaginary parts (μ″, ε″) reflect the magnitude of the ability to dissipate electromagnetic waves. In Tables 1-3 and 1-6, the ε′ of the sample in Comparative Example 1 shows a decreasing trend, while the ε′ of the sample in Example 3 tends to level off. This indicates that the dispersion characteristics of the sample obtained by adding the coated iron-zinc alloy to the coating are improved.

[0055] In Examples 1-3, the imaginary part (ε″) of the dielectric constant of the samples tended to decrease with increasing amount of aminosilane. This is because the thin film formed by the self-assembly of aminosilane isolates the contact between iron-zinc alloy particles, reducing the dielectric loss of the material. The results of Example 4 show that different aminosilane structures or increasing the amount of surface coating will increase the dielectric loss of the resulting microwave absorbing material, which is not conducive to the application of electronic products.

[0056] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A novel low-frequency absorbing material, characterized in that, The coating comprises a PET double-sided adhesive substrate and a sheet-like microwave absorber, wherein the microwave absorber-containing coating uses acrylic resin, amino resin and cellulose resin as the matrix, and sheet-like iron-aluminum alloy modified by an aminosilane surface coating process as the sheet-like microwave absorber as the filler.

2. The novel low-frequency absorbing material according to claim 1, characterized in that, The method for preparing the microwave absorber includes the following steps: S1: Mix zinc sulfate and ferrous sulfate according to Zn 2+ Fe 2+ The ferric zinc alloy powder is prepared by dissolving a metal ion in deionized water at a molar ratio of 0.25-0.30:0.7-0.75 to form a salt solution with a metal ion concentration of 1 mol / L. NaOH is added to the hydrazine hydrate solution to adjust the pH to 8-12, and then the solution is heated to 80-100℃. The salt solution is added dropwise and kept at this temperature for 0.5-1.5 h. After the solution color changes completely, the precipitate is filtered, washed until neutral, and the resulting powder is dried to obtain iron-zinc alloy powder. S2: Using methanol as a solvent, prepare an aminosilane solution with a volume fraction of 20-50%, and then add the iron-zinc alloy powder obtained in S1 to the aminosilane at a mass ratio of 1:2.5-4. After stirring and reacting for 24 hours, a mixed slurry is obtained. S3: After filtering, washing, and drying the mixed slurry obtained in S2 with high-concentration nitrogen, the resulting paste is dried, crushed, and sieved in a constant temperature and atmospheric pressure environment to obtain the microwave absorber.

3. The novel low-frequency absorbing material according to claim 2, characterized in that, The aminosilane mentioned in S2 is at least one of 3-aminopropyltrimethoxysilane, N-methyl-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, di(3-trimethoxysilylpropyl)amine, (N,N-dimethyl-3-aminopropyl)trimethoxysilane, N,N-diethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropyltriethoxysilane, and N-methyl-3-aminopropyltriethoxysilane.

4. The novel low-frequency absorbing material according to claim 2, characterized in that, The drying temperature described in S3 is 80-100℃, and the drying time is 6-8h.

5. The novel low-frequency absorbing material according to claim 1, characterized in that, The preparation method of the coating containing the microwave absorber includes the following steps: SS1: Add the organic solvent into the reaction vessel and stir until homogeneous. Then add the cellulose resin and stir for 1-2 hours until completely dissolved. Then add the acrylic resin and amino resin in sequence and stir for 1-3 hours until fully mixed. SS2: Add the microwave absorber to the resin system obtained in SS1 and stir until it is evenly dispersed; SS3: Add the functional additive to the reaction vessel and stir evenly to obtain the coating containing the microwave absorber.

6. The novel low-frequency absorbing material according to claim 5, characterized in that, The organic solvent mentioned in SS1 is at least one of acetone, isopropanol, n-butanol, propylene glycol methyl ether, ethyl acetate, and n-butyl acetate, and is used in a percentage of 8-25% by mass of the coating containing the microwave absorber.

7. The novel low-frequency absorbing material according to claim 5, characterized in that, The acrylic resin in SS1 has an acid value of 7-9 mgKOH / g and is used at a mass percentage of 10-15% of the coating containing the microwave absorber; the cellulose resin is obtained by mixing cellulose acetate butyrate and cellulose acetate propionate in a mass ratio of 0.5-1.7:1-5 and is used at a mass percentage of 1-5% of the coating containing the microwave absorber; the amino resin is urea-formaldehyde resin and is used at a mass percentage of 5.5-10% of the coating containing the microwave absorber.

8. The novel low-frequency absorbing material according to claim 5, characterized in that, The microwave absorber used in SS2 is 45-70% by mass of the coating containing the microwave absorber.

9. The novel low-frequency absorbing material according to claim 5, characterized in that, The functional additives described in SS3 include at least one of leveling agents, softening agents, and drying agents.

10. A method for preparing the novel low-frequency absorbing material according to any one of claims 1-9, characterized in that, The process includes the following steps: coating a material containing a microwave absorber onto the surface of a release film made of PET double-sided adhesive, and curing it to obtain the novel low-frequency microwave absorbing material.